Post-processing of cold sprayed CoNiCrAlY coatings on Inconel 718 by rapid induction heating - Yang, Yongjing (2022)
Cold spray is a solid-state additive manufacturing process that has been increasingly used for restoration of damaged parts. Due to the nature of powder solid-state bonding, cold spray coatings usually possess pores in the microstructures. Heat treatment has been widely used as a post-processing method to reduce the porosity of cold sprayed coatings. However, it usually requires the whole component to be treated in the furnace and typically takes a few hours to finish the treatment. This study aims to develop a localized and rapid post-processing method for cold sprayed coatings. Multi-layer cold sprayed coatings of CoNiCrAlY on an Inconel 718 substrate were produced. Then the coatings were heat treated at 800◦ C, 900◦ C, 1000◦ C and 1100◦ C by rapid induction heating. The porosity level of the coatings reduced significantly after induction heating for a short period of merely 10 min. This is attributed to the preferential Joule heating at pore regions, which results in pore closures within the coatings. The potential application of induction heating as a rapid post-processing method for cold spray coatings has been demonstrated in this work.